E-1: THE RIBA CASE AND THE DISCOURSE ON DEVELOPMENT OF ISLAMIC LAW - Gillani, Syed Hasnat Ahmad shah; Atta Ul Mustafa; Gardazi, Syed Mudasser Fida (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2022)
The recent decision from one of the apex courts of Pakistan hailed as a landmark ruling, infect validates the practical viability of an interest-free economy. The Federal Shariat Court has directed the government to adopt Shari’ah-compliant modes in the future while borrowing either from domestic or from foreign sources. The five years deadline is given to adopt such models. It is apprehended that the verdict has opened up new avenues for the realization of the Riba free trance which can be treated as a stepping-stone by the government and all stakeholders collectively to further build upon. In this context, the research endures to present the discourse on development of Islamic commercial law from its sources to shaping into a legal system. More specifically, it focuses on theory of adaptability of contemporary Islamic law and principles of modern legal system in contemporary transactions.